Advancing Nursing Education Through Entrustable Professional Activities: Bridging Academic Education and Clinical Training. - Chia-Chuan CHANG; Yueh-Er CHIOU; Xin-Yi LIU (Journal of Nursing, 2025)
The gap between classroom learning and clinical practice has presented a challenge to nursing education for decades, posing significant risks to patient safety and care quality--particularly in light of the chronic global shortage of nursing professionals. Entrustable Professional Activities (EPAs) offer a competency-based approach to bridging this gap by assessing whether learners can independently perform essential clinical tasks in authentic care settings, thereby guiding appropriate levels of supervision and delegation. In Taiwan, EPAs, which have been preliminarily implemented in the context of newly graduated nurse and clinical preceptor training, have demonstrated potential benefits in both competency assessment and nurse retention. Notably, countries such as the Netherlands and Singapore have successfully integrated EPAs into nursing education, highlighting their adaptability in addressing workforce shortages and supporting professional development. The aim of this article is to explore the application of EPAs in nursing education, offering nursing educators new insights on strategies for enhancing curriculum assessment and professional entrustment. By integrating EPAs into nursing education, the goal is to cultivate clinical competencies in nursing professionals more effectively, close the theory--practice gap, and thus better ensure patient safety and the quality of care.